Optical probing of gastrocnemius in patients with peripheral artery disease characterizes myopathic biochemical alterations and correlates with stage of disease. Issue 5 (14th March 2017) - Becker, Ryan A.; Cluff, Kim; Duraisamy, Nithyanandhi; Mehraein, Hootan; Farhoud, Hussam; Collins, Tracie; Casale, George P.; Pipinos, Iraklis I.; Subbiah, Jeyamkondan
Abstract: Peripheral artery disease (PAD) is a condition caused by atherosclerotic blockages in the arteries supplying the lower limbs and is characterized by ischemia of the leg, progressive myopathy, and increased risk of limb loss. The affected leg muscles undergo significant changes of their biochemistry and metabolism including variations in the levels of many key proteins, lipids, and nucleotides. The mechanisms behind these changes are poorly understood. The objective of this study was to correlate the severity of the PAD disease stage and associated hemodynamic limitation (determined by the ankle brachial index, ABI) in the legs of the patients with alterations in the biochemistry of chronically ischemic leg muscle as determined by ATR‐Fourier transform infrared micro‐spectroscopy. Muscle (gastrocnemius) biopsies were collected from 13 subjects including four control patients (ABI≥0.9), five claudicating patients (0.4 ≤ ABI<0.9), and four critical limb ischemia (CLI) patients (ABI<0.4). Slide mounted specimens were analyzed by ATR‐Fourier transform infrared micro‐spectroscopy. An analysis of variance and a partial least squares regression model were used to identify significant differences in spectral peaks and correlate them with the ABI. The spectra revealed significant differences ( P  < 0.05) across control, claudicating, and CLI patients in the fingerprint and functional group regions. Infrared microspectroscopic probing of ischemic muscle biopsies demonstrates that PAD produces significant and unique changes to muscle biochemistry in comparison to control specimens. These distinctive biochemical profiles correlate with disease progression and may provide insight and direction for new targets in the diagnosis and therapy of muscle degeneration in PAD. Abstract : This study characterizes the degree of myopathy as it relates to progression in Peripheral artery disease (PAD) using ATR‐FTIR microspectroscopy. Spectral signatures taken from muscle tissue samples predicted hemodynamic limitation and progression of the disease. The spectral biomarkers investigated may provide insight into new therapeutic targets.